Critical ethnography and education - Carspecken, Phil Francis, 1951-; Walford, Geoffrey (Studies in educational ethnography ;, 2001)
Volume five of this expanding series of books draws together a collection of papers based on a particular form of critical ethnography developed by Phil Francis Carspecken and his colleagues at the University of Houston. Each chapter is based on a unique field project conducted in the Houston area which was planned and conducted by its particular author, but each chapter shares and exemplifies a common methodological theory. The Houston version of critical ethnography attempts to deal with some challenges from certain feminist and postmodern writers about the validity of qualitative research, and the authors argue that clear methods and standards exist for conducting qualitative studies such that well supported findings may be distinguished from highly questionable ones. Following an initial chapter by Carspecken which outlines the theory and methodology adopted, are seven case studies which cover such topics as multicultural literature, the supervision of teachers in training, school restructuring, charter schools, and race and standardized testing.